Assessment of modelling strategies for film cooling. Issue 5 (2nd May 2017) - Mazzei, Lorenzo; Andreini, Antonio; Facchini, Bruno
Abstract : Purpose: Effusion cooling represents one the most innovative techniques for the thermal management of aero-engine combustors liners. The huge amount of micro-perforations implies a significant computational cost if cooling holes are included in computational fluid dynamics (CFD) simulations; therefore, many efforts are reported in literature to develop lower-order approaches aiming at limiting the number of mesh elements. This paper aims to report a numerical investigation for validating two approaches for modelling film cooling, distinguished according to the way coolant is injected (i.e. through either point or distributed mass sources). Design/methodology/approach: The approaches are validated against experimental data in terms of adiabatic effectiveness and heat transfer coefficient distributions obtained for effusion cooled flat plates. Additional reynolds-averaged naver stokes (RANS) simulations were performed meshing also the perforation, so as to distinguish the contribution of injection modelling with respect to intrinsic limitations of turbulence model modelling. Findings: Despite the simplified strategies for coolant injection, this work clearly shows the feasibility of obtaining a sufficiently accurate reproduction of coolant protection in conjunction with a significant saving in terms of computational cost. Practical/implications: The proposed methodologies allow to take into account the presence of film cooling in simulations of devices characterized by a huge number of holes. Originality/value: This activity represents the first thorough and quantitative comparison between two approaches for film cooling modelling, highlighting the advantages involved in their application.